Effect of Gamma Rays Irradiation to Cipedak Avocado Genetic Diversity - Farihul Ihsan; Sumeru Ashari; Andy Soegianto; Sukartini Sukartini; Affandi Affandi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Avocado cv. Cipedak is a superior cultivar that match the preferences of Indonesian consumers. However, it has several weaknesses, such as low edible portion, thin skin, and short fruit shelf life. One effort to improve the character weakness is by mutation breeding using gamma ray irradiation. Induction of mutation by gamma ray irradiation at a dose of 10 Gy was conducted on Cipedak avocado shoots in October 2021 which produced 13 first generation avocado mutants (M1). Observation on leaves morphological characters and DNA analysis were needed to find out the changes level of genetical diversity. The research was conducted in Cukurgondang Research Station and Molecular Laboratory of Indonesian Tropical Fruits Research Institute from January to March 2022. The plant material used involved 13 M1 progenies and cv. Cipedak. The material used were 20 weeks old grafted plants. The observed variables were macro and micromorphological characters as well as DNA-RAPD analysis. The results showed that there were phenotypic and genotypic changes in 13 M1 avocados seedlings. The coefficients of differences on macro and micromorphological characters were up to 33% and 28%, respectively and the coefficient of difference for DNA-RAPD analysis was 74%.